A 2007 Social Accounting Matrix (SAM) for Vietnam - Arndt, Channing; Garcia, Andre; Pham, Hoang Ha; McCoy, Simon; Tarp, Finn; Thurlow, James (University of Copenhagen, 2010)
This paper documents a Vietnam Social Accounting Matrix (SAM) for the year 2007. The national SAM is based on newly estimated supply-use tables, national accounts, state budgets, and balance of payments. The SAM reconciles these data using cross-entropy estimation techniques. The final SAM is a detailed representation of Vietnam's economy. It separates 63 activities and commodities; rural/urban labor by different education levels; and households by rural/urban areas and farm/nonfarm expenditure quintiles. Labor and household information is drawn from the 2006 Vietnam Household Living Standards Survey. Finally, the SAM identifies government, investment and foreign accounts. It is therefore an ideal tool for economywide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.